PERU AS WORLD-LEVEL FIRST EXPORTER OF QUINUA - Ku Soria, Pamela (2017)
Quinoa (Chenopodium quinoa) is a native Andean food plant, originally from the contours of Lake Titicaca in Peru and Bolivia that was part of the basic diet of the prehispanic population and still present in the preparation of dishes. It is now known worldwide for its high nutritional content, valued for food security. The aim is to describe the evolution of Peruvian quinoa exports of the two main sub tariff headings, identifying the most significant importing countries and regions producing quinoa in the coast, highlands and forest. It is relevant because exports increased significantly since 2013 declared “International Year of Quinoa” by the UN; then the CCL reported that in 2014 and 2015, Peru became the world’s largest exporter and is looking to continue this growth in a sustainable manner. The type of study is descriptive, not experimental, with a hypothetical deductive method, the population comprised all ex post facto data. The conclusion is that the product has expanded to different world markets where its biggest buyer is the United States, cultivated mainly in the Puno region and currently all over our country.